KONSTRUKSI WAKAF SECARA FIKIH - Jaenudin Jaenudin (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2019)
Abstract: Endowments (waqf) in Islamic law is an importent act, done by wakif as eternal good deeds, to promote economic equality of the people. It has been carried out from the beginning of Islam, being developed up to the present time. By reviewing library materials related to waqf, it was found that waqf law has its own characteristics. Commonly, endowments are binding and should not be traded, but in Hanafi schools of thought, waqf is seen as a ghair lazim contract. Because of its unique and important position, the waqf law needs to be studied thoroughly, and should be designated as special law.Abstraks: Perwakafan dalam hukum Islam merupakan salah satu bagian penting dalam mewujudkan keadilan ekonomi serta amal kebajikan yang terus berlangsung bagi wakif. Wakaf telah dilaksanakan sejak masa Nabi saw dan terus berkembang pada masa sahabat dan generasi setelahnya. Dengan penulusuran bahan pustaka yang terkait permasalahan hukum wakaf, ditemukan bahwa hukum wakaf memiliki ciri tersendiri dari hukum kebendaan (fikih muamalat). Di satu sisi, wakaf bersifat mengikat tidak boleh diperjualbelikan, tetapi pada madzhab Hanafi wakaf dipandang sebagai akad ghair lazim. Kerana kedudukannya yang unik dan penting, hukum wakaf secara fikih dikaji secara menyeluruh, bahkan dalam wakaf juga dilegilasi menjadi hukum yang khusus.